Synthesis, Chracterization and Applications of Coated Composite Materials for Energy Applications - Dubal, Deepak; Ahmad, Awais (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The formulation of coated composite materials is an important field of research around the world today. Coated composite materials include inhomogeneous and anisotropic materials. These materials are formulated by an amalgamate minimum of two or more materials that accommodate different properties. These materials have a vast field of appealing applications that encourage scientists to work on them. Due to their unique properties, such as their strength, liability, swiftness, and low cost, they are used as promising candidates for reliable applications in various fields, such as biomedical, engineering, energy devices, wastewater treatment, and agriculture. Different types of composite materials have had a noticeable impact in these fields already, such as glass, plastic, and, most promisingly, metal oxide nanoparticles.